Ременные гарнитуры гуннской эпохи Азиатского Боспора - Строков, А.А. (Боспорские исследования, 2009)
The article is dedicated to the analysis of various details of belt fittings found in the territory of Asian Bosporus and dated back to the second half of 4th - early 6th centuries AD. For classification of buckles we have used the method proposed by A.V. Bogachev. Based on the combination of several features, we point out twenty seven variants. Almost all of them were made of bronze and had a movable frame, a plate and a tongue. Buckles and other belt details are of key importance in dating of archaeological complexes. The study has shown that several buckles might be dated back to the middle - second half of 6th century, and that the great majority of them could be synchronized with D2 phase of Middle European chronological system (380/400 - 440/450 AD), and only a few of them were dated back to a later period - the second half of 5th - early 6th centuries AD.